HIERARCHICAL REPRESENTATION STUDY ON PERSONAL MOTIVES OF SUMMER HOLIDAY SEEKERS: THE CASE OF ITALY DURING THE COVID-19 PANDEMIC - Zira Hichy; Marco Platania (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Using a method that examines goal setting, this study investigates the reasons people take a holiday during the ‘COVID summer’. Participants were 141 Italians that completed a questionnaire during summer 2020. The results revealed 13 reasons for taking a holiday: ‘Family/Friends’, ‘Attachment’, ‘Relax’, ‘Fun’, ‘New experiences’, ‘Increasing knowledge’, ‘Overcoming general stress’, ‘Overcoming lockdown stress’, ‘Present well-being’, ‘Future well-being’, ‘Enrichment’, ‘I like it’, and ‘Socialising’. Revealing connections between reasons, the hierarchical structure revealed that the principal reasons for taking a holiday during the COVID summer are tied to gaining future well-being, maintaining close relationships, and enhancing personal growth. These results are useful for defining tourism destination policies in the post-pandemic phase.